Emergency response and communication during Bili-Bili Dam flood crisis in Indonesia - Saleh, Rahmita; Yusmanizar (Penerbit Universiti Kebangsaan Malaysia, 2019)
The high rainfall intensity in the South Sulawesi region in January 2019 has increased the water level of the Bili-Bili Dam. It has raised alert status and enforced the Dam manager to carry out emergency responses and open the spillway to anticipate water overflow which has ultimately caused floods in the Gowa Regency area. This study aims to describe and analyze the emergency responses and communications carried out by Balai Besar Wilayah Sungai Pompengan Jeneberang (BBWSPJ), as the manager of the Bili-Bili Dam, in dealing with the crisis. The research has applied case study approach, using in-depth interviews and document analysis. The study finds that the emergency responses are carried out based on the Emergency Action Plan and Standard Operational Procedures documents. The responses should involve some related government bodies. There are four levels of hazard status, namely normal, wary, alert, and caution. The higher status would involve the higher government bureaucracy. The study also finds that local people are posited merely as audience or object of the emergency responses. This study proposes that crisis awareness needs to be shared to all stakeholders through developing and implementing appropriate crisis communication planning. Involving locals and stakeholders will provide public understanding about what kind of crisis is happening and what are the right actions should be taken. The role of public relations should be highlighted to increase public trust in the organization's ability to manage the crisis.